Infective endocarditis of an aortic bioprosthesis causing life-threatening incessant junctional tachycardia: a case report. Issue 6 (30th November 2020) - Chatelain, Quentin; Carcaterra, Andrea; Rey, Florian; Burri, Haran
Abstract: Background : Infective endocarditis with paravalvular abscess can be complicated by atrioventricular block (AVB), but junctional ectopic tachycardia (JET) has as yet never been described. Case summary : A 68-year-old male recently admitted with Staphylococcal aureus endocarditis of his aortic valve bioprosthesis, presented with a regular tachycardia at 240 b.p.m. with a pre-existent right bundle branch block pattern. Haemodynamic collapse necessitated electrical cardioversion, following which high-grade AVB was observed. Multiple recurrences of the same tachycardia required repeated electrical cardioversions and emergent electrophysiological study, which indicated JET. The tachycardia was unresponsive to overdrive pacing, adenosine and intravenous amiodarone, and external cardioversions. Radiofrequency catheter ablation of the atrioventricular node was performed emergently with interruption of the tachycardia. A temporary external pacemaker was implanted via a jugular route. The tachycardia recurred after 48 h at a slower rate, and the patient underwent redo ablation. Transoesophageal echocardiography revealed a pseudoaneurysm of the right sinus of Valsalva probably corresponding to an evacuated abscess. A permanent pacemaker was implanted after active infection had been ruled out. At 3 months of follow-up, the patient had complete AVB, without arrhythmia recurrence. Discussion : This is the first case report of JET complicating a paravalvular abscess of the aortic valve with concomitant AVB. Junctional ectopic tachycardia is very rare arrhythmia which is usually seen in children as a congenital arrhythmia or following surgical correction of paediatric heart disease. The differential diagnosis is discussed in detail in the article.